Melt compounding with graphene to develop functional, high-performance elastomers - Araby, Sherif; Zaman, Izzuddin; Meng, Qingshi; Kawashima, Nobuyuki; Michelmore, Andrew; Kuan, Hsu-Chiang; Majewski, Peter; Ma, Jun; Zhang, Liqun (IOP Publishing, 2013)
Rather than using graphene oxide, which is limited by a high defect concentration and cost due to oxidation and reduction, we adopted cost-effective, 3.56 nm thick graphene platelets (GnPs) of high structural integrity to melt compound with an elastomer—ethylene–propylene–diene monomer rubber (EPDM)—using an industrial facility. An elastomer is an amorphous, chemically crosslinked polymer generally having rather low modulus and fracture strength but high fracture strain in comparison with other materials; and upon removal of loading, it is able to return to its original geometry, immediately and completely. It was found that most GnPs dispersed uniformly in the elastomer matrix, although some did form clusters. A percolation threshold of electrical conductivity at 18 vol% GnPs was observed and the elastomer thermal conductivity increased by 417% at 45 vol% GnPs. The modulus and tensile strength increased by 710% and 404% at 26.7 vol% GnPs, respectively. The modulus improvement agrees well with the Guth and Halpin-Tsai models. The reinforcing effect of GnPs was compared with silicate layers and carbon nanotube. Our simple fabrication would prolong the service life of elastomeric products used in dynamic loading, thus reducing thermosetting waste in the environment.